Asymmetric Decentralization in Aceh: Institutionalization of Conflict of Interest by Elites of GAM - Utama, Bayu Satria (UI Scholars Hub, 2019)
This article explains an institutionalization of conflicts in the implementation of special autonomy in Aceh Province. In general, one of the objectives of implementing the asymmetric decentralization policy is to resolve the problem of national integration between Free Aceh Movement (GAM) and the Government of Indonesia. However, the implementation of asymmetric decentralization in Aceh Province presents a different phenomenon. Although there is conflict resolution between GAM and the Government of Indonesia, the conflict dynamics change into a conflict of interest between GAM elites at the local level as part of the dynamics of electoral politics. This article is based on a literature study on secondary data to understand the electoral politics process has evolved to be a medium for institutionalizing conflict after the separatism movement in Aceh. This article shows that the understanding of asymmetric decentralization in Aceh Province not only served as a solution to the conflict between GAM and the Indonesian Government but also became a medium for institutionalizing conflict between GAM’s elite exponents through local elections in 2006–2017.